El maltrato animal visto a través del arte de la pintura - Sizalima Becerra, Noelia Lisbeth (Machala : Universidad Técnica de Machala, 2022)
The present degree work called animal abuse seen through the art of painting,animal abuse as part of social violence,has created an environment of abuse, pain and suffering towards the dog. tracking through the collection of stray dogs is directed mainly with the purpose of showing a social problem in a different way. It is about animal abuse,where the problem is sought to exhibit it in an unusual way, for which an artistic manifestation such as performance is used.this is an ephemeral art that has greater strength when in the artistic representation the individual reacts and interact with her.for this,it was essential to investigate this problem in depth. In the content of the investigation it will be possible to find the diverse ways in which the mistreatment by man towards animals is continuously shown, evidencing with concrete facts that have arisen within ecuador,it is very unfortunate to appreciate this type of information through newspapers,where some case of abuse are for profit. when talking about mistreatment,reference is made to abandonment, poisoning, running over by motor vehicles,inhumane treatment in agro-industries in animals for consumption,buying and selling of pets,commercialization of wildlife,there are many causes of mistreatment that occur and are not gives it due importance.It is this reality that is not token very much into account that is sought to be shown through an artistic interpretation in real time in front of society,hoping that the individual will react to it. The human being,being a thinking being with the ability to discern between good and bad actions,is the main aggressor.The development of the artistic proposal was made a work of art representing animal abuse and the reaction of the individual seeing that so much violence and little importance around the development of the performance.Art allows human beings to manifest themselves in various ways,but for a good representation,research is necessary, it is good to verify all the informatio, in this way it will be possible to have optimal results that respond according to the in terms of the theme and the problem.The purpose of assessing the reactions to the problem,verifying what is the value that is given when we deal with a theme about animals,will it be that there is a probability of causing some impact or it will go unnoticed in front ot society.What will be the individuals actions,what will be the causes that lead the human being to act in an anthropocentric way,always putting their needs first,before those of the animals.It is important to consider that animals have the right to well-being,to have a home,to receive care,love and health.The work is exhibited in real time and through a virtual platform,being able to verify the reactions online and live. In addition,photographic records of the work will be shown that show acting live in this situation,culminating in a critical aproach.
El presente trabajo de titulación denominado El maltrato animal visto a través del arte de la pintura, El maltrato animal como parte de la violencia social, ha creado un entorno de abuso, dolor y sufrimiento hacia el perro. Seguimiento a través de la recopilación, de perros callejeros, está dirigido principalmente con el propósito de mostrar de una manera distinta una problemática social. Se trata del maltrato animal, en donde se busca la problemática exhibirlo bajo una manera poco cotidiana, para ello se hace uso de una manifestación artística como lo es performance. Este es un arte efímero que tiene mayor fuerza cuando en la representación artística el individuo reacciona e interactúa frente a ella. Para ello fue fundamental indagar a profundidad dicha problemática. En el contenido de la investigación se podrá encontrar las diversas maneras en la que continuamente se muestra el maltrato por parte del hombre hacia los animales, evidenciando con hechos concretos que han suscitado dentro del Ecuador, es muy lamentable apreciar este tipo de información por medio de periódicos, en donde algunos casos de maltrato son con fines lucrativos. Cuando se habla del maltrato se hace referencia al abandono, envenenamiento, atropello con automotores, al trato inhumano en agroindustrias en animales de consumo, compra y venta de mascotas, comercialización de vida silvestre, son muchas las causas de maltrato que se dan y no se le da la debida importancia. Es esa realidad que no es tomada muy en cuenta la que se busca mostrar mediante una intervención artística en tiempo real frente a la sociedad, esperando que el individuo reaccione frente a ello. El ser humano siendo un ser pensante con capacidad de discernir entre las buenas y malas acciones, es el principal agresor. El desarrollo de la propuesta artística se realizó una obra de arte representando al maltrato animal y la reacción del individuo viendo que tanta violencia y poca importancia en torno al desenvolvimiento del performance. El arte permite al ser humano manifestarse de diversas formas, pero para una representación buena es necesaria la investigación, es bueno constatar toda la información, de ese modo se podrá tener resultados óptimos que respondan de acuerdo a la necesidad en cuanto a la temática y el problema. La finalidad de valorar las reacciones frente a la problemática, constatar cual es el valor que se da cuando tratamos una temática sobre los animales, será que exista la probabilidad de causar algún impacto o pasará desapercibida frente a la sociedad. Cuál será el actuar del individuo, cuáles serán las causas que le lleven al ser humano a actuar de manera antropocéntrica anteponiendo siempre sus necesidades primordialmente, antes que las de los animales. Es importante considerar que los animales tienen derecho a un bienestar, a tener vivienda, a recibir cuidado, amor y a la salud. La obra es expuesta en tiempo real y mediante una plataforma virtual, pudiendo constatar las reacciones online y en vivo. La obra es expuesta en tiempo real y mediante una plataforma virtual, pudiendo constatar las reacciones online y en vivo. Además, se mostrarán registros fotográficos de la obra que muestren el actuar en vivo ante esta situación, culminando con un abordaje crítico.
Keywords: LEY; PROTECCION ANIMAL; MALTRATO ANIMAL; SENSIBILIZACION